Model reševanja konfliktov - primer lesnega podjetja na Hrvaškem - Faletar, Josip (Acta silvae et ligni, 2016)
In business, as well as in all other relationships, there are different opinions and conflicts. Dealing with conflicts is one of the most important tasks of management which has a great influence on efficiency and success of a company. In the research, which was a subject of this article, we were studying the phenomena of conflict in a big wood industry company in Croatia. Data were collected by structured questionnaire survey. We were trying to establish characteristics of an existing model of dealing with conflicts in this particular company. We were more focused on relationship between employees, how often conflicts occur and how persons involved in conflict respond to it. Since in this particular company the model for dealing with conflicts formally does not exist, based on the research we were able to identify the model and prove its characteristics. Results showed that relationship between employees in researched company were good and that responses to conflicts were positive. The most frequent cause for conflicts is a poor information flow between employees, which showed the existing need for improving communication channels, especially by conversations and different meetings. Therefore, communication channels are one of the most important elements of the new model for solving conflict situations in this particular company.
Keywords: konflikti; conflicts; reševanje konfilktov; leadership; lesno podjetje; wood industry; model; modeli; Croatia; Hrvaška; poslovanje; vodenje